LOCAL BUDGET REVENUES IN THE CONVENTION OF THE COVID-19 PANDEMIC - Dmytrovska, V.S.; Kokhan, I.V. (The actual problems of regional economy development, 2020)
An article devoted to the study of the involvement of the structure and identification of trends in the formation of local budget revenues in the context of the coronavirus pandemic (COVID-19). Features of replenishment of the revenue side of local budgets, the main sources of revenue in the process of budget decentralization: data on income of individuals, promotional data, land fees, uniform data and data on real estate, other than land. A number of budget monetary units of the legislation aimed at counteracting pandemics and their impact on the input part of the budgets of the united territorial communities are described. The receipts of the budgets of the united territorial communities for 9 months of 2019-2020 were analyzed and the impact of the COVID-19 pandemics on the achievement of local budget revenues was assessed. A detailed analysis of the formation of local budgets' own revenues showed that in terms of local budgets in 2019-2020, the highest growth rate of personal income tax and local taxes and fees in local budgets of the united territorial communities. These results indicate the participation and interest of local authorities in accumulating most of the revenues of the budgets of the united territorial communities, taking measures to find reserves for their revenues in the context of the COVID-19 coronavirus pandemic and the effectiveness of the fiscal role of taxes and fees. The authors substantiate the directions of overcoming the negative consequences of the COVID-19 pandemic on the revenue side of local budgets through the fiscal mechanism and the settlement of inter-budgetary relations. The methodological basis of this study are such methods as empirical research (monitoring, comparison measurement); theoretical research (deductive and axiomatic method, idealization); general methods used at the empirical and theoretical level of research (analysis, analogy, abstraction, concretization, synthesis, induction, deduction).